Characterization of Chilean patients with sporadic colorectal cancer according to the three main carcinogenic pathways: Microsatellite instability, CpG island methylator phenotype and Chromosomal instability. Issue 7 (July 2020) - Wielandt, Ana María; Hurtado, Claudia; Moreno C, Mauricio; Villarroel, Cynthia; Castro, Magdalena; Estay, Marlene; Simian, Daniela; Martinez, Maripaz; Vial, Maria Teresa; Kronberg, Udo; López-Köstner, Francisco
Molecular classification of colorectal cancer is difficult to implement in clinical settings where hundreds of genes are involved, and resources are limited. This study aims to characterize the molecular subtypes of patients with sporadic colorectal cancer based on the three main carcinogenic pathways microsatellite instability (MSI), CpG island methylator phenotype (CIMP), and chromosomal instability (CIN) in a Chilean population. Although several reports have characterized colorectal cancer, most do not represent Latin-American populations. Our study includes 103 colorectal cancer patients who underwent surgery, without neoadjuvant treatment, in a private hospital between 2008 and 2017. MSI, CIN, and CIMP status were assessed. Frequent mutations in KRAS, BRAF, and PIK3CA genes were analyzed by Sanger sequencing, and statistical analysis was performed by Fisher's exact and/or chi-square test. Survival curves were estimated with Kaplan–Meier and log-rank test. Based on our observations, we can classify the tumors in four subgroups, Group 1: MSI-high tumors (15%) are located in the right colon, occur at older age, and 60% show a BRAF mutation; Group 2: CIN-high tumors (38%) are in the left colon, and 26% have KRAS mutations. Group 3: [MSI/CIN/CIMP]-low/negative tumors (30%) are left-sided, and 39% have KRAS mutations; Group 4: CIMP-high tumors (15%) were more frequent in men and left side colon, with 27% KRAS and 7% presented BRAF mutations. Three percent of patients could not be classified. We found that CIMP-high was associated with a worse prognosis, both in MSI-high and MSI stable patients (p = 0.0452). Group 3 (Low/negative tumors) tend to have better overall survival compared with MSI-high, CIMP-high, and CIN-high tumors. This study contributes to understanding the heterogeneity of tumors in the Chilean population being one of the few characterizations performed in Latin-America. Given the limited resources of these countries, these results allow to improve molecular characterization in Latin-American colorectal cancer populations and confirm the possibility of using the three main carcinogenic pathways to define therapeutic strategies.